(3GdbGYOI GdhGSWIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hcai hSdGe Ydi YHGOg GdPjf EUWai CeG HYO agPg QSGdI ai eSFdg QLdjf JfGXQG abGd CMOgeG dGHO dfG ef hGSWI HjffG hHjf Gddg aEfG dGfbOQ Cf fUd Zdjg HZjQ Pdc GdLhGH s
(3BNQgG (B:s
(3hgPg GdLed dgG SHW dG JMJedg gPg GdhQbI hGddg CYde abW hGdMeO ddg hMOg hUdi Gddg JYGdi Ydi SjOfG eMeO hBdg hSde hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds